Factors that Influence Farmers in Farming Bird’s Chili in Zed Village, Mendo Barat District, Bangka Regency - amilia yanti; Yulia; Iwan Setiawan (Journal of Integrated Agribusiness, 2026)
Chili pepper is a horticultural commodity with high economic value and is widely cultivated by farmers in various regions, including Zed Village, Mendo Barat District, Bangka Regency. However, farmers' decisions to plant chili peppers are influenced by various factors. This study aims to describe the stages of chili pepper cultivation in Zed Village and the factors that encourage farmers to plant chili peppers in Zed Village. The research method used is a survey method with sampling using a saturated census with 45 respondents. Data collection methods used observation, interviews, questionnaires, and descriptive qualitative analysis. The results of the study indicate that the stages of chili pepper cultivation in Zed Village start from sowing, land preparation, planting, maintenance, fertilization, pest and disease control, and then harvesting. Factors that encourage farmers to plant chili peppers in Zed Village are age, land area, experience, social environment, and selling price. The results of this study also emphasize the important role of innovation, institutional support, and increasing farmer capacity in encouraging the development of cayenne pepper farming in the research area.